Characterization of Java Island's volcanoes based on volcano density and quantification of volcanic products using Landsat imagery - Supriyadi; Asep Saepuloh; Harry Mahardika; Wahyu Srigutomo (Geosystems and Geoenvironment)
Java Island has 34 volcanoes that the twenty of them are the most active termed as type-A. The process of volcano generation and the characteristics of Java Island as part of the Sunda Arc produce Quarternary volcanoes from the western to the eastern land. Remote sensing provides an opportunity to characterize volcanoes all over Java Island by analyzing the occurrences of their volcanic products. In this study, we have characterized spatially of the volcanoes expressed by volcano density or sum of volcanoes per area (i.e., 0.5° × 0.5° or 3098.04 km2). The Landsat 8 and 9 OLI data were processed and displayed in False Color Composite (FCC) R, G, B for Band 5, 6, 7 to identify volcanic products distribution. The True Color Composite (TCC) R, G, B for Band 4, 3, 2 was also used to identify vegetation cover affected by volcanic products. The FCC assisted by TCC images were used visually to determine the boundaries of the volcanic products area, calculate their coverage area, determine the main flow directions, and maximum length. The calculated volcano density map shows that the Java Quaternary volcanoes were divided into three segments. The western segment is the highest density about five volcanoes, the central segment varies between one and three volcanoes, and the eastern segment is about two volcanoes per area. The volcanic products were successfully identified by seventeen out from twenty volcanoes. The large area of volcanic products such as Mt. Guntur (12,287,138 m2), Mt. Merapi (18,258,542 m2), and Mt. Semeru (18,645,778.3 m2) are associated with explosive eruption. Combining main flow direction and volcano density shows that the volcanic products in the northern edge are predominantly directed to NW. In contrast, they vary towards NE, SE, SW, and NW in the southern edge.